Analisis Kompetensi Tim Rescue Dinas Pemadam Kebakaran dan Penyelamatan Kota Surabaya Pasar Turi - Amri, Achmad Syaiful (Seminar Nasional Manajemen, 2025)
This study aims to analyze the Competence and abilities of each member of the Rescue Team of the Surabaya City Fire and Rescue Service. The research data was obtained through a research method using a population and sample of a number of Rescue Team personnel, along with the Squad Commander, Head of Human Resource Development, and Head of Rescue as research objects. From the beginning of the study, learning to the results of the training showed an increase in the abilities of each individual personnel and team. At the beginning of the training, it was seen that out of 48 personnel, only 10% were considered to understand the activity, but the implementation of the training activities in a disciplined and routine manner resulted in 98% of the 48 personnel being able to carry out activities and increase their abilities. From the results of the competency analysis, the leader must hold education/training and training routinely and in stages so that the abilities of the Rescue Team members can be evenly distributed..